Certain Nonlinear Integral Inequalities and Their Applications. (19th January 2017) - Tian, Yazhou; Fan, Min; Sun, Yuangong
Abstract : Several new retarded integral inequalities of Gronwall-Bellman-Pachpatte type are presented which generalize the inequalities to the more general nonlinear case in the literature and provide explicit bounds on unknown functions. These results include many existing ones as special cases and can be used as tools in the qualitative analysis of certain classes of integrodifferential equations.